MENINGKATKAN KEMAMPUAN SISWA MENYELESAIKAN PERHITUNGAN UNTUNG ATAU RUGI DALAM PERDAGANGAN DENGAN MENGGUNAKAN PERSENTASE MELALUI METODE PEMBERIAN TUGAS PADA KELAS VII A MTS ALKHAIRAAT PUSAT PALU - ,, Aspar (Kreatif, 2014)
Abstract : The study is classroom action research. It aims at improving students’ ability in comleting/finising provit and loss calculation in trade by using percentage through assignment/task method (metode pemberian tugas). The subjeck of the study is student of VII A of MTs Alkhairaat Pusat Palu. The problem of the study is the lack of students’ ability in completing/finising provit and loss calculation using percentage and its Application. Alternative of the problem used in the study is by appling assignment study method. Based on the observation done during the study, it indicates that there is improvement of the students’ ability in completing/finising provit and loss calculation in trade ranging from first and second cycle. Before the cycle implemented (preliminary study), it was found out that the students’ mastery learning was 20% or 6 students, that there were 80 % of the students or 24 students. Who did not gain the mastery learning and that the students’ classical absorption was 52,5%. The result obtained in the first cycle was that the students’ mastery learning was 36,67% or 11 students’ that there were 63,33% of the student or 27 students who did not achieve the mastery learning, and that the students classical absorption was 65,56%. While in the second cycle, it was found out that, the students’ mastery learning was 90% of the students (36 students), that there were 10% of the students (4 students) who did not gain the mastery learning, and that the students classical absorption was 87,17%. This the final result of the study it could be concluded that there wen students’ improvement dealing with their classical absorption in comleting/finising provit and loss calculation, that was 26,60%. Keyword : Method of assignment, Mastery Learning, Classical absorption